First Genome Sequences of Two Multidrug-Resistant Candida haemulonii var. vulnera Isolates From Pediatric Patients With Candidemia - Rodrigues, Luiza Souza; Gazara, Rajesh Kumar; Passarelli-Araujo, Hemanoel; Valengo, Andressa Eloisa; Pontes, Paula Veronesi Marinho; Nunes-da-Fonseca, Rodrigo; de Souza, Robson Francisco; Venancio, Thiago Motta; Dalla-Costa, Libera Maria (Frontiers in Microbiology, 2020)
Candida haemulonii is a complex formed by C. haemulonii sensu stricto, C. haemulonii var. vulnera, and C. duobushaemulonii. Members of this complex are opportunistic pathogens closely related to C. pseudohaemulonii, C. lusitaniae, and C. auris, all members of a multidrug-resistant clade. Complete genome sequences for all members of this group are available in the GenBank database, except for C. haemulonii var. vulnera. Here, we report the first draft genomes of two C. haemulonii var. vulnera (isolates K1 and K2) and comparative genome analysis of closely related fungal species. The isolates were biofilm producers and nonsusceptible to amphotericin B and fluconazole. The draft genomes comprised 350 and 387 contigs and total genome sizes of 13.21 and 13.26 Mb, with 5,479 and 5,507 protein-coding genes, respectively, allowing the identification of virulence and resistance genes. Comparative analyses of orthologous genes within the multidrug-resistant clade showed a total of 4,015 core clusters, supporting the conservation of 24,654 proteins and 3,849 single-copy gene clusters. Candida haemulonii var. vulnera shared a larger number of clusters with C. haemulonii and C. auris; however, more singletons were identified in C. lusitaniae and C. auris. Additionally, a multiple sequence alignment of Erg11p proteins revealed variants likely involved in reduced susceptibility to azole and polyene antifungal agents. The data presented in this work will, therefore, be of utmost importance for researchers studying the biology of the C. haemulonii complex and related species.